Enhancing Students’ Reading Comprehension Ability Through Comparison Study Between Cooperative Learning Numbered Heads Together (NHT) and Thin-Pair-Share (TPS) Strategies - Mokodompit, Prisilia L. (Acuity: Journal of English Language Pedagogy, Literature and Culture, 2016)
This study attempts to find significance difference in enhancing students’ reading comprehension ability by comparing two teaching methods: Numbered Heads Together (NHT) and Think-Pair-Share (TPS). In this study, the respondents were students of Grade VIII from SMP Advent II, Setia Budi and students of Grade VIII from SMPN 1, parongpong. After careful detail of analysis, the result found is the average gain for Numbered Heads Together group is 0.2553 and Think-Pair-Share group is 0.5127. The p-value = 0.001 < Î± (0.05), which means there is a significant difference on the students’ ability in reading comprehension between those who are taught using Numbered Heads Together (NHT) method and those who are taught using Think-Pair-Share (TPS) method. Keywords: Numbered Heads Together, Think-Pair-Share, Reading Comprehension.